2012
DOI: 10.5861/ijrsp.2012.251
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Filipino adolescents’ conception of happiness

Abstract: The current paper aimed to explore the meaning and conception of happiness among selected Filipino adolescents. Ten Filipino college students whose ages range between 16 and 20 were selected through purposive sampling. The study employed qualitative-descriptive research design. Findings showed that happiness is a multifaceted construct that involved the following major themes: satisfaction of wants, absence of worries, expression of positive emotions, motivational drive, and fulfillment of relational needs. Di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 18 publications
2
18
0
2
Order By: Relevance
“…However, results from previous queries were not ubiquitous. The varied findings may have stemmed from the complexity of happiness that is characterized by multiple influential factors (Datu & Valdez, 2012). In some studies, happiness was found to be associated with academic performance (Manzoor, Siddique, Riaz, & Riaz, 2014;Mohammadi, 2015) and academic motivation (Hassanzadeh & Mahdinejad, 2013).…”
Section: Happiness and Academic Performancementioning
confidence: 99%
See 1 more Smart Citation
“…However, results from previous queries were not ubiquitous. The varied findings may have stemmed from the complexity of happiness that is characterized by multiple influential factors (Datu & Valdez, 2012). In some studies, happiness was found to be associated with academic performance (Manzoor, Siddique, Riaz, & Riaz, 2014;Mohammadi, 2015) and academic motivation (Hassanzadeh & Mahdinejad, 2013).…”
Section: Happiness and Academic Performancementioning
confidence: 99%
“…In the Philippine context where happiness is associated with the motivational drive (Datu & Valdez, 2012), happy students may be more academically motivated. Internal motivation, in turn, may boost academic performance (Khoshnam, Ghamari, & Gendavani, 2013.…”
Section: International Journal Of Research Studies In Psychology 71mentioning
confidence: 99%
“…Thoilliez (2011) stated that children between 6 and 12 years of age explain happiness through family, friends, enjoyment, academic success and helping others; Giacomoni, Souza and Hutz (2014) stated that Brazilian children aged 6-12 describe happiness as positive feelings, lack of violence, being with friends, and participating in fun activities; and Uusitalo-Malmivaara (2014) reported that 9th grade students expressed that the things that make them happy are success at school, more leisure time, friendship, physical appearance, family environment and having plans for the future, respectively. Datu and Valdez (2012) found that adolescents describe happiness as satisfaction of needs, lack of negative feelings, expressing positive feelings and meeting their relational needs, and that they think personal qualities of happy adolescents are being helpful, cheerful, optimistic and expressive of one's positive feelings, and the behaviors are helping others, laughing and having fun, making people happy and avoiding negative thoughts. In addition, Işık and Üzbe Atalay (2017), came up with the findings that the things that make children between 10 and 15 years old happy are discovering that they are talented in a subject, engaging in fun activities, spending time with family and friends, being healthy, giving and receiving presents, and academic success.…”
Section: Introductionmentioning
confidence: 99%
“…In Datu and Valdez's (2012) study of ten Filipino adolescents, they found that the adolescents' definitions of happiness included the 'satisfaction of wants', 'absence of worries', 'expression of positive emotions', 'a motivational drive' and 'fulfillment of relational needs'. The last definition pertains to interacting with a social support system composed of family, friends, peers and colleagues.…”
Section: Self-actualization As a Motivation For Growthmentioning
confidence: 99%
“…Opportunities to interact with family elders and extended family -When asked how the families taught their children about their culture, they specified that aside from being close to their families (Datu & Valdez, 2012), all of the MSYAs studied in Philippine schools. The school curriculum incorporates Filipino values (e.g., the use of Filipino courteous language characterized by the words "po" and "opo") and indigenous games, dances, songs, and folklore; and other traditions related to Filipino heritage.…”
Section: B Growth Motivationmentioning
confidence: 99%